KONFORMITAS TEMAN SEBAYA DENGAN PROKRASTINASI AKADEMIK PADA SISWA SMP DI SURABAYA - Ilham Yusril Ramadhan; Firsty Oktaria Grahani; Ardianti Agustin (Fakultas Psikologi Universitas Wijaya Putra, 2023)
Time management that is less effective and efficient in the learning process is one of the problems that students often experience. It is like doing fun habits or activities with friends so they ignore the assignments given, low student interest in doing teacher assignments, resulting in delaying time to do assignments known as procrastination. This study aims to determine whether there is an influence of peer conformity with academic procrastination in Muhammadiyah 14 Surabaya Junior High School students. The research subjects consisted of 42 male students and 48 female students, using the incidental method. Data were collected through questionnaires measuring peer conformity, and academic procrastination. Data analysis used simple linear regression analysis techniques with the help of the SPSS for Windows programme. The hypothesis results showed that p-value=0.008<0.05, which indicates the influence of peer conformity with academic procrastination. The coefficient of determination (R square) of 0.008 shows that peer conformity has a weak effect of 0.008%, while the remaining 0.092% is influenced by other factors not examined in this study. the conclusion, peer conformity has a low effect on academic procrastination 0.008%, this is because there are other factors that influence academic procrastination besides peer conformity and can be used as a study for further researchers.